Eicosapentaenoic acid-rich oil supplementation activates PPAR-γ and delays skin wound healing in type 1 diabetic mice - Burger, Beatriz; Sagiorato, Roberta Nicolli; Silva, Jéssica Rondoni; Candreva, Thamiris; Pacheco, Mariana R.; White, Daniel; Castelucci, Bianca G.; Pral, Laís P.; Fisk, Helena L.; Rabelo, Izadora L. A.; Elias-Oliveira, Jefferson; Osório, Wislei Riuper; et al. (Frontiers in Immunology, 2023)
Delayed wound healing is a devastating complication of diabetes and supplementation with fish oil, a source of bioactive omega-3 (-3) fatty acids, including eicosapentaenoic acid (EPA), seems an appealing strategy for these patients due to potential anti-inflammatory effects. In contrast to this view, some recent studies have shown that -3 fatty acids may have a deleterious effect in skin repair. However, the effects of oral administration of EPA on wound healing in the diabetic condition are unclear. We used streptozotocin-induced diabetic mice to investigate the effects of oral administration of an EPA-rich oil on wound closure and quality of new tissue formed. Gas chromatography (GC) analysis in serum and skin showed that EPA-rich oil increased the incorporation of ω-3 and decreased ω-6 fatty acids, resulting in a reduction in the ω-6/ω-3 ratio. On the 10th day after wounding, EPA increased the production of IL-10 by neutrophils in the wound, reduced collagen deposition, and ultimately delayed wound closure and impaired the quality of the healed tissue. EPA increased IL-10 production by neutrophils during tissue repair, and this effect was PPAR-γ-dependent. EPA and IL-10 reduced collagen production by fibroblasts in vitro. In vivo, topical PPAR-γ-blockade reversed the deleterious effects of EPA on wound closure and on collagen organization in diabetic mice. We also observed a reduction in IL-10 production by neutrophils in diabetic mice treated topically with PPAR-γ blocker. This study shows that oral supplementation with EPA-rich oil impairs skin wound healing in diabetes, acting on inflammatory and non-inflammatory cells. Importantly, we revealed that PPAR-γ inhibition could be a therapeutic target for treating impaired wound healing in diabetes.